Equilibrium unemployment and retirement - Jean-Olivier Hairault; François Langot; Andre Zylberberg (Institute for the Study of Labor (IZA), 2012)
As a preliminary step, we first provide some new empirical evidence that labor market conditions affect retirement decisions at the individual level: unemployed people are more likely to retire. Our main objective in this paper is then to propose an equilibrium unemployment approach to retirement decisions that allows us to unveil the factors which explain why unemployed workers choose to retire earlier and the conditions under which this behavior is optimal. Two main conclusions emerge: the retirement decision of unemployed workers depends on the labor-market frictions whereas that of employed workers does not; the existence of search externalities makes the retirement age of unemployed workers intrinsically suboptimal. Considering Social Security policy issues, we show that the complete elimination of the implicit tax on continued activity is not necessarily welfare-optimizing in a second best world where the labor market equilibrium suffers from distortions.
urn:nbn:de:101:1-201208096293
Keywords: J22; J26; H55; 330; search; matching; retirement; Social Security; Altersgrenze; Arbeitslosigkeit; Arbeitsuche; Arbeitsmarkt; Gleichgewicht; Theorie